PENGEMBANGAN INSTRUMEN KETERBUKAAN DIRI BERBASIS MEDIA PERMAINAN DAM QUIZ PADA PESERTA DIDIK TINGKAT SMP - Icha Anindya Vania Salsabila; Risaniatin Ningsih; Khususiyah Khususiyah; Laelatul Arofah (Management of Education: Jurnal Manajemen Pendidikan Islam, 2023)
Self-disclosure is needed to build interpersonal relationships with other individuals. In the process of adaptation to the social environment, a person must be willing to open up so that his presence can be accepted in his environment. This study aims to develop and validate self-disclosure instruments for junior high school students. This development research was carried out at Al Huda Lamongan Islamic Middle School. The method used in this research is R&D. The trial was carried out on 47 students using saturated sampling techniques. Aspects of self-disclosure that are measured in the instrument include: emotional state, interpersonal relationships, personal, taste, sex, thoughts, religion, problems, and education. The results of this data analysis mean that the self-disclosure instrument for junior high school students can be declared valid and reliable, so that it can be used by counseling teachers and counseling researchers to measure the level of self-disclosure of students.